DETERMINANTS OF QUALITY OF LIFE OF LOW BACK PAIN PATIENTS - Julianti, Hari Peni; Hadisaputro, Soeharyo; Susanto, Hardhono; Tulaar, Angela Bibiana Maria; Athaya, Arina Rezky (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Low back pain (LBP) is a common condition that leads to significant physical and mental health challenges worldwide. It is the primary contributor to years lived with disability (YLDs) and adversely affects quality of life (QoL). In Indonesia, there is a lack of research on the factors affecting QoL among patients with LBP. Objective:  This study aims to investigate the factors that influence the QoL of LBP patients at William Booth Hospital in Semarang, Indonesia. Methods: An analytic observational study with a cross-sectional design was conducted from July to August 2023, involving 95 LBP patients. Data were collected using questionnaires, including the SF-36v1 for QoL assessment. The data were analyzed using chi-square tests and binary logistic regression to identify significant determinants. Results:  The study found that 82.1% of respondents reported poor physical health, while 87.4% indicated good mental health. Factors such as older age, subacute to chronic LBP, severe pain, low education levels, and dependency in daily living activities significantly impacted the physical health domains. No significant associations were observed between QoL and gender, BMI, or occupational risk. Severe pain and limited independence in daily tasks emerged as critical determinants of reduced QoL. Conclusion: The findings emphasize the need for targeted interventions, such as pain management, rehabilitation programs, and educational initiatives, to enhance the QoL of LBP patients—especially among older adults and those with low education levels. These measures are essential to reduce the socioeconomic burden of LBP in Indonesia.